2015
DOI: 10.1002/hbm.22853
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity associated with hand shape generation: Imitating novel hand postures and pantomiming tool grips challenge different nodes of a shared neural network

Abstract: Functional connectivity analysis revealed that during hand shape generation the BOLD-response of every region correlated significantly with every other area regardless of the hand posture task performed, although some regions were more involved in some hand postures tasks than others.Based on between-task differences in functional connectivity we predict that imitation of novel hand postures would suffer most from left superior parietal disruption and that pantomiming hand postures for tools would be impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…The superior parietal cortex is involved in the central processes for writing [Planton et al, 2013; Sugihara et al, 2006; Sakurai et al, 2007], which is confirmed by the increase of activation in this area for the contrast writing versus zigzagging. The language related processes for writing refer to stored knowledge about orthographic and phonological processes gained over repetitive encounters [Vingerhoets and Clauwaert, 2015], independently from the effector used to write. This suggests that this area plays a minor role in specific motor processes during online execution of dominant handwriting.…”
Section: Discussionmentioning
confidence: 99%
“…The superior parietal cortex is involved in the central processes for writing [Planton et al, 2013; Sugihara et al, 2006; Sakurai et al, 2007], which is confirmed by the increase of activation in this area for the contrast writing versus zigzagging. The language related processes for writing refer to stored knowledge about orthographic and phonological processes gained over repetitive encounters [Vingerhoets and Clauwaert, 2015], independently from the effector used to write. This suggests that this area plays a minor role in specific motor processes during online execution of dominant handwriting.…”
Section: Discussionmentioning
confidence: 99%
“…This is unfortunate since RBD patients and right brain stimulations are often associated with defective imitation (De Renzi, 1980;Goldenberg, 1999;Stamenova et al, 2010). Further studies are now required to disentangle (Kubiak & Króliczak, 2016) (Adamovich, August, Merians, & Tunik, 2009) (Jackson, Meltzoff, & Decety, 2006) (Koski, Iacoboni, Dubeau, Woods, & Mazziotta, 2003) (Krüger et al, 2014) (Mühlau et al, 2005) (Montgomery, Isenberg, & Haxby, 2007) (Montgomery & Haxby, 2008) (Suchan, Melde, Herzog, Hömberg, & Seitz, 2008) (S Tanaka, Inui, Iwaki, Konishi, & Nakai, 2001) (Shigeki Tanaka & Inui, 2002) (Vingerhoets & Clauwaert, 2015) (Watanabe et al, 2011) (Mengotti, Corradi-Dell'Acqua, et al, 2013)…”
Section: Conclusion and Clinical Considerationsmentioning
confidence: 99%
“…2018 ). Furthermore, an emerging literature demonstrates that there is increased functional connectivity between the left inferior parietal lobule and left posterior middle temporal gyrus when neurotypical participants gesture the use of tools ( Vingerhoets and Clauwaert 2015 ; Garcea et al. 2018 ; Hutchison and Gallivan 2018 ) and in resting-state fMRI ( Simmons and Martin 2012 ).…”
Section: Introductionmentioning
confidence: 99%